2013
DOI: 10.1038/cr.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Activation of lysosomal function in the course of autophagy via mTORC1 suppression and autophagosome-lysosome fusion

Abstract: Lysosome is a key subcellular organelle in the execution of the autophagic process and at present little is known whether lysosomal function is controlled in the process of autophagy. In this study, we first found that suppression of mammalian target of rapamycin (mTOR) activity by starvation or two mTOR catalytic inhibitors (PP242 and Torin1), but not by an allosteric inhibitor (rapamycin), leads to activation of lysosomal function. Second, we provided evidence that activation of lysosomal function is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
267
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(302 citation statements)
references
References 58 publications
31
267
4
Order By: Relevance
“…However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion. 41 Thus, the observed induction of autophagyand lysosome-related transcripts in colchicine-treated fish could result from a compensatory mechanism to rescue a dysfunctional autophagic-lysosomal function. Finally, while we cannot account for all the cellular and metabolic perturbations induced by the long term use of colchicine, we speculate that induction of ER stress may also affect major cellular functions, such as apoptosis or chaperone-mediated autophagy (CMA), that crosstalk with autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase of lysosomal transcripts was not followed by an increase of the lysosomal function (as evidenced by the activity of CTSD), in line with the demonstrated inhibition of the autophagic flux in our samples and the recently published data showing that activation of lysosomal function depends on autophagosome-lysosome fusion. 41 Thus, the observed induction of autophagyand lysosome-related transcripts in colchicine-treated fish could result from a compensatory mechanism to rescue a dysfunctional autophagic-lysosomal function. Finally, while we cannot account for all the cellular and metabolic perturbations induced by the long term use of colchicine, we speculate that induction of ER stress may also affect major cellular functions, such as apoptosis or chaperone-mediated autophagy (CMA), that crosstalk with autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired autophagic flux at the late stage is closely related with lysosomal dysfunction. A previous study demonstrated that lysosomal function was activated in the course of autophagy via mTORC1 suppression and autophagosome-lysosome fusion [31] . In this study, SpostC activated lysosomal function in the autophagy process, which was characterized by a decrease in p62 levels as well as increased expression and activation of cathepsin B ( Figure 3D-3F and Figure 5D-5F).…”
Section: Discussionmentioning
confidence: 99%
“…9,[26][27][28][29][30][31][32] The role of the v-ATPase in MTORC1 activation is unequivocal and well described for multiple cell lines. 4 However, mutations in genes encoding GATOR1 proteins, makes MTORC1 signaling resistant to a v-ATPase inhibitor, thereby providing a possibility that v-ATPase-dependent MTORC1 regulation might differ in different cellular settings.…”
Section: V-atpase Inhibitors and Mtorc1 Signaling Pathway Activationmentioning
confidence: 99%